REQUIRED EFFECTIVE TEMPERATURE SUM FOR SUNFLOWER VARIETIES - Yuldasheva Zulfiya Kamalovna (Modern American Journals, 2025)
The article experimentally revealed that the Dilbar variety of oil sunflower receives more effective temperature during the growing season than the Buzuluk and Zarrin varieties. In the variants with a sowing norm of 50, 60 and 70 thousand seeds/ha, it was observed that the temperature was higher when sowing on April 15 than when sowing on April 1 and May 1, while in the variant with a sowing norm of 80 thousand seeds/ha, on the contrary, a lower temperature was required. The Zarrin variety was distinguished from the experimental varieties by its early ripening and shorter days for transition from phase to phase. However, the pattern of higher effective temperature requirements was preserved in the variants with a higher sowing norm compared to the variants with a lower sowing norm.